'Take my kidneys but not my corneas'—Selective preferences as a hidden problem for 'opt‐out' organ donation policy. (27th May 2022) - Williams, Nicola Jane; Manson, Neil C.
Abstract: With aims to both increase organ supply and better reflect individual donation preferences, many nations worldwide have shifted from 'opt‐in' to 'opt‐out' systems for post‐mortem organ donation (PMOD). In such countries, while a prospective donor's willingness to donate their organs/tissues for PMOD was previously ascertained— at least partially —by their having recorded positive donation preferences on an official register prior to death, this willingness is now presumed or inferred— at least partially —from their not having recorded an objection to PMOD —on an official organ donation register. Using evidence regarding the presence and prevalence of selective donation preferences, and via exploration of how appeals to donation preferences are used to both motivate and legitimate shifts to opt‐out frameworks, this paper draws attention to a set of previously unexplored problems for opt‐out organ donation arising in contexts where: (a) individuals demonstrate selective post‐mortem organ/tissue donation preferences, (b) legislation provides prospective donors with the opportunity to selectively permit / refuse the donation of certain organs/tissues in line with these preferences. While selective preferences pose few problems for opt‐in systems where a selective occasion is built into the process of signing the donor register, this is not the case for opt‐out systems. The loss of this selective occasion can cause significant problems where appeals to preferences motivate/legitimate shifts to opt‐out but evidence regarding variable preferences does not feed into determinations regarding organ/tissue exclusions. The nature of these problems depends on how the authorization aspect of 'opt‐out' systems is framed (e.g. as presumed consent, deemed consent or, given the role of familial consent in many jurisdictions as consent in name only).